Tumor Dormancy, Quiescence, and Senescence, Volume 2 2013
DOI: 10.1007/978-94-007-7726-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Function of the ING Proteins in Cancer and Senescence

Abstract: Age is one of the strongest correlates to the incidence of cancers known, suggesting that the two processes are linked. Cell aging (senescence) is increasingly being linked to epigenetic pathways, many of which have recently been found to be markedly altered in precancerous and cancer cells. Thus, misregulation of epigenetic pathways may impact both cancer and aging by infl uencing genetic and biochemical pathways common to both processes. Similar to the p53 and retinoblastoma (Rb) tumor suppressors that affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Several studies demonstrated that INGs could enhance apoptosis via the death receptor-mediated extrinsic pathway (Fas/caspase-8 apoptosis pathway) in different cancers [19,20]. Our in vitro and in vivo data indicate that ING4 overexpression could increase the expression of Fas, an important member of the tumor necrosis factor receptor superfamily, which is involved in apoptosis.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies demonstrated that INGs could enhance apoptosis via the death receptor-mediated extrinsic pathway (Fas/caspase-8 apoptosis pathway) in different cancers [19,20]. Our in vitro and in vivo data indicate that ING4 overexpression could increase the expression of Fas, an important member of the tumor necrosis factor receptor superfamily, which is involved in apoptosis.…”
Section: Discussionmentioning
confidence: 52%